The silver gene of Drosophila melanogaster encodes multiple carboxypeptidases similar to mammalian prohormone-processing enzymes. - Settle, S H (1995)
The silver (svr) gene of Drosophila melanogaster is required for viability, and severe mutant alleles result in death prior to eclosion. Adult flies homozygous or hemizygous for weaker alleles display several visible phenotypes, including cuticular structures that are pale and silvery in color due to reduced melanization. We have identified and cloned the DNA encoding the svr gene and determined the sequence of several partially overlapping cDNAs derived from svr mRNAs. The predicted amino acid sequence of the polypeptides encoded by these cDNAs indicates that the silver proteins are members of the family of preprotein-processing carboxypeptidases that includes the human carboxypeptidases E, M, and N. One class of svr mRNAs is alternatively spliced to encode at least two polyproteins, each of which is composed of two carboxypeptidase domains.